Prickly ash seeds can promote healthy production of sheep by regulating the rumen microbial community - Li, Dengpan; Li, Qiao; Ma, Xueyi; Wang, Huihui; Wang, Chunhui; Wang, Haoyu; Liu, Zhanjing; Li, Taotao; Ma, Youji (Frontiers in Microbiology, 2024)
The aim of this study was to investigate the effect of prickly ash seeds on rumen microorganisms of Hu sheep by adding different ratios of prickly ash seeds, and to make some research on the relationship between rumen flora and production performance. Twenty-seven male lambs of Hu sheep were divided into three groups fed with 0%, 3%, and 6% of prickly ash seeds for 90 days. At the end of the feeding trial, rumen fluid was collected from six sheep in each group for 16S amplicon sequencing. The results showed that the addition of prickly ash seeds significantly increased both Chao1 and ACE indices (P < 0.05), and the differences between groups were greater than those within groups. The relative content of Bacteriodota at the phylum level decreased, and the relative content of Fusobacteriota, Proteobacteria, Acidobacteriota, and Euryarchaeota increased. The relative content of Papillibacter and Saccharofermentans was increased at the genus level, and the relative content of Bacteroides and Ruminococcus was decreased. The test group with 3% of prickly ash seeds was superior to the test group with 6% of prickly ash seeds.In addition, the addition of 3% of prickly ash seeds was able to improve the metabolism or immunity of sheep. Fusobacteriota and Acidobacteriota were positively correlated with The total weight, Dressing percentang, and Average Daily Gain (ADG), and negatively correlated with Average Daily Feed Intake (ADFI), Feed to Gain ratio (F/G), and lightness (L*). Methanobrevibacter, Saccharofermentans were positively correlated with ADG, and negatively correlated with ADFI and L*. In conclusion, under the present experimental conditions, the addition of prickly ash seeds was able to increase the abundance and diversity of rumen microorganisms in Hu sheep and change the relative abundance of some genera. However, the addition of 6% prickly ash seeds may negatively affect the digestive and immune functions in the sheep rumen.